Household Impacts of Tariffs : Data and Results from Agricultural Trade Protection - Artuc, Erhan; Porto, Guido; Rijkers, Bob (World Bank, Washington, DC, 2019)
How do trade reforms impact households in different parts of the income distribution? This paper presents a new database, the Household Impacts of Tariffs data set, which contains harmonized household survey and tariff data for 54 low- and lower-middle income countries. The data cover highly disaggregated information on household budget and income shares for 53 agricultural products, wage labor income, nonfarm enterprise sales and transfers, as well as spending on manufacturing and services. Using a stylized model of the first-order impacts of import tariffs on household real income, this paper quantifies the welfare implications of agricultural trade protection. On average, unilateral elimination of agricultural tariffs would increase household incomes by 2.50 percentage points. Import tariffs have highly heterogeneous effects across countries and within countries across households, consumers, and income earners; the average standard deviation of the gains from trade within a country is 1.01 percentage points.